Analisis Kinerja Keuangan Bank Dalam Menghadapi Isu Resesi Ekonomi (Tahun 2019-2022): (Studi Kasus Pada PT. Bank Mandiri Tbk.) - Ari Siswati; Dewi Ariani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Banks are a source of information about a bank's financial position, performance and changes in a bank's financial position which are very useful for assessing a bank's financial performance. This research aims to analyze the financial performance of PT. Bank Mandiri Tbk. In this research, the method used is a quantitative method in the form of PT financial report data. Bank Mandiri Tbk which was published on the Indonesia Stock Exchange from 2019 to 2022. This study uses an analysis of the Return Of Assets (ROA) ratio, Capital Adequacy Ratio (CAR) and Non Performing Loans (NPL). it can be concluded that the financial performance of PT Bank Mandiri Tbk can be stated to be in good condition and can restore financial performance and is already prepared to face the issue of economic recession after the Covid-19 pandemic.